Distance Education and Learning (DEL) in The Master of Law Program in Facing Challenges in The Era of Disruption - Sri Wahyu Kridasakti; Purwaningdyah Murti Wahyuni; Megafury Apriandini; Nadia Nurani Isfarin; Madiha Dzakiyyah Chairunnisa (Nurani Hukum, 2022)
Facing the Industrial Revolution 4.0/5.0 the development of information and communication based on the internet and digital encourages people's lives more advanced and various functions of life are more effective and efficient, the use of internet and digital media makes the boundaries that can hinder movement and distance can be removed and bring the world closer to unlimited reach. In the development of Education, it is also encouraged to be able to adapt by leaving the conventional education system to a system based on distance education and learning/DEL, in distance education and learning/DEL the education system will be carried out openly and remotely which will eliminate distance and restrictions for someone in the learning and teaching process, therefore education will be faster, efficient, precise and low cost. This research is legal research with normative juridical approach, the data used are primary data and secondary data are analyzed using quantitative analysis. The first result: the use of distance education and learning/DEL is a form of educational transformation in the face of the era of disruption, where the education system is carried out remotely using the help of instruction technology based on transformation, research, assessment, evaluation and memory subsystem with the help of internet technology. Second: distance education and learning/DEL is able to be a solution for geographical and topographical problems in Indonesia, so that anyone can achieve a master of law with the help of distance education and learning/DEL technology.